Analysis of the Effect of Environmental Performance and Total Asset Turnover on the Profitability of Energy Companies Listed on the Indonesian Stock Exchange in 2019-2021 - Ayuning Larasati; Ruslan Abdul Ghofur; Evi Ekawati (Newinera Publisher, 2023)
A company is an organization that carries out activities or operations to achieve certain goals. The growth of advanced industry is directly proportional to the increase in pollution arising from industrial production processes, such as production waste, which can increase air and water pollution to dangerous levels. This research aims to test and analyze the influence of environmental performance and total asset turnover on profitability. This research uses a sample of 10 energy companies listed on the IDX for three years. The research method used in this research is the fixed effect model (FEM). The data analysis technique uses panel data regression with the help of the e-viewers12 software tool. The research results show that the FEM statistical results show that the environmental performance variable has a significant positive effect on company profitability, and the total asset turnover variable significantly positively affects company profitability with a confidence level of 85 percent. Then, the simultaneous test (F test) shows that the environmental performance variables and total asset turnover do not affect the company's profitability.